(untitled) (Heritage, 2024)
The problem of the work is the analysis of the application of some of the "soft power" instruments of the United Kingdom of Great Britain on the territory of the Republic of Serbia. From the point of view of influence on the realization of its vital interests and the defense of statehood, through the protection of the territorial sovereignty and territorial integrity of the Republic of Serbia. Although Britain’s geopolitical influence is not primarily directed towards Serbia and is not the focus of Serbian contemporary diplomacy, by analyzing various historical-political relationships, indirect influence through the application of "soft power" instruments, i.e. the operation of covert instruments of power, social and educational institutions, non-governmental organizations, intelligence components, placement of interests through the KFOR mission on the territory of AP Kosovo and Metohija and other factors. Pointing out that although Serbia is a small, strategically almost negligible country, it plays an important role in the realization of Britain’s interests in this part of Europe. The political noise that shapes the daily life of Serbia, the daily political topics that take us away from the real focus cannot deny the constant existence of British interests on the territory of the Republic of Serbia. Interests de facto exist, but they are realized through the use of power instruments that are not direct and completely transparent.